The role of human factors and ergonomics in mining emergency management: three case studies. (1st January 2013) - Horberry, Tim; Xiao, Tania; Fuller, Ruth; Cliff, David
Mining is a complex and hazardous work domain. This paper presents three related research studies in mining emergency management, highlighting the contribution that human factors and ergonomics are making to this field. The first study investigates the challenges associated with the collection and management of information during underground coal mining emergencies from a human-centred perspective. The second and third case studies build on the first study: the second one focuses on decision making deficiencies in incident management teams and the final one examines organisational issues related to mining control rooms during emergencies. In each of these three research studies, the broad problem is first defined, then the work undertaken and results produced are described, and finally the implications and future work are presented. Following this, the human factors contributions to help create safe and efficient mining emergency management systems are discussed.